Shooting star : Annie Oakley, the legend - Dadey, Debbie; Goto, Scott (New York : Walker and Co., 1997)
An exaggerated account of the life and exploits of the sharp-shooting entertainer.
School Library Journal starred.
Booklist.
Bulletin (Center for Children's books).
4.1
K-3
Keywords: Oakley, Annie, -- 1860-1926 -- Juvenile literature; Oakley, Annie, -- 1860-1926.; Oakley, Annie, -- 1860-1926.; Shooters of firearms -- United States -- Biography -- Juvenile literature; Women entertainers -- United States -- Biography -- Juvenile literature; Sharpshooters; Entertainers; Women -- Biography; Sharpshooters -- Biography; Entertainers -- Biography; Women -- Biography; Sharpshooters; Entertainers; Women -- Biography